Implementation of tourism village management policies based on Edward III's theory in Bintan Regency to achieve sustainable tourism - Yusnita, Yeni; Annabila, Raudah Zahra (CV. Austronesia Akademika, 2024)
Tourism villages have emerged as a crucial source of local income in Bintan Regency, yet the policy implementation for managing these villages faces both practical and theoretical challenges. This research aims to analyze the implementation of public policies in the management of tourist villages in Bintan, using Edward III's theory as a framework. The research employs a descriptive qualitative method, utilizing both secondary data from government documents and primary data collected through interviews with key informants. The findings reveal that although Bintan’s tourism villages are generally managed effectively, several obstacles still hinder their full potential. These challenges include limited human resources, inadequate infrastructure, budgetary constraints, and social conflicts within the community. The study highlights the importance of communication as a key factor in policy implementation, where efficient and effective communication between stakeholders can improve service quality in the tourist villages. It also raises community awareness about the preservation of the environment and local culture, which are vital for attracting tourists. Moreover, the availability of both human and natural resources plays a significant role in enhancing tourist experiences. The attitudes and dispositions of tourism village managers are also essential in fostering an environment that supports environmental conservation and cultural heritage. The research underscores the need for a structured bureaucratic framework, characterized by clear policy hierarchies, active community involvement, government transparency, and better collaboration among agencies. To promote sustainable tourism in Bintan, this study recommends that the government provide training and support to local communities.